Soft x-ray microscopy with 7 nm resolution - Roesner, Benedikt; Finizio, Simone; Koch, Frieder; Doring, Florian; Guzenko, Vitaliy A.; Langer, Manuel; Kirk, Eugenie; Watts, Benjamin; Meyer, Markus; Lorona Ornelas, Joshua; Späth, Andreas; Stanescu, Stefan; et al. (Optica, 2020)
The availability of intense soft x-ray beams with tunable energy and polarization has pushed the development of highly sensitive, element-specific, and noninvasive microscopy techniques to investigate condensed matter with high spatial and temporal resolution. The short wavelengths of soft x-rays promise to reach spatial resolutions in the deep single-digit nanometer regime, providing unprecedented access to magnetic phenomena at fundamental length scales. Despite considerable efforts in soft x-ray microscopy techniques, a two-dimensional resolution of 10 nm has not yet been surpassed in direct imaging. Here, we report on a significant step beyond this long-standing limit by combining newly developed soft x-ray Fresnel zone plate lenses with advanced precision in scanning control and careful optical design. With this approach, we achieve an image resolution of 7 nm. By combining this highly precise microscopy technique with the x-ray magnetic circular dichroism effect, we reveal dimensionality effects in an ensemble of interacting magnetic nanoparticles. Such effects are topical in current nanomagnetism research and highlight the opportunities of high-resolution soft x-ray microscopy in magnetism research and beyond. (C) 2020 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2020-12-18